Gaming science: the “Gamification” of scientific thinking - Morris, Bradley; Croker, Steve; Zimmerman, Corinne; Gill, Devin; Romig, Connie (Frontiers in Psychology, 2013)
Science is critically important for advancing economics, health, and social well being in the 21st century. A scientifically literate workforce is one that is well suited to meet the challenges of an information economy. However, scientific thinking skills do not routinely develop and must be scaffolded via educational and cultural tools. In this paper we outline a rationale for why we believe that video games have the potential to be exploited for gain in science education. The premise we entertain is that several classes of video games can be viewed as a type of cultural tool that is capable of supporting three key elements of scientific literacy: content knowledge, process skills, and understanding the nature of science. We argue that there are three classes of mechanisms through which video games can support scientific thinking. First, there are a number of motivational scaffolds, such as feedback, rewards, and flow states that engage students relative to traditional cultural learning tools. Second, there are a number of cognitive scaffolds, such as simulations and embedded reasoning skills that compensate for the limitations of the individual cognitive system. Third, fully developed scientific thinking requires metacognition, and video games provide metacognitive scaffolding in the form of constrained learning and identity adoption. We conclude by outlining a series of recommendations for integrating games and game elements in science education and provide suggestions for evaluating their effectiveness.